1997
DOI: 10.1017/s0967199400003725
|View full text |Cite
|
Sign up to set email alerts
|

Glycine and methionine transport by bovine embryos

Abstract: As glycine is one of the most concentrated amino acids in the female genital tract, we investigated its uptake by bovine in vitro matured /in vitro fertilised blastocysts in the presence of increasing concentrations of radiolabelled glycine. We also determined methionine uptake by in vitro and in vivo produced embryos. In our study, the hypothesis of more than one site of enzyme activity for glycine substrate was not validated. We determined a V max of 23.4fmol/min per embryo and a K m value of 13.3 uM. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As mentioned, CSF is responsible for the meiosis arrest in unfertilized oocytes, and its inactivation by a surge of Ca 2+ during fertilization releases the oocyte from this arrest [ 109 ]. Methionine and cysteine can affect glutathione levels which prevent the negative effects of ROS and apoptosis in embryos [ 29 , 80 , 118 , 135 , 136 ]. Recent evidence suggested that the polarized protein like leptin and signal transducer and activator of transcription 3 (STAT3) and maybe beta-actin and IL-1 mRNAs can display polarized distribution in oocytes [ 137 139 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, CSF is responsible for the meiosis arrest in unfertilized oocytes, and its inactivation by a surge of Ca 2+ during fertilization releases the oocyte from this arrest [ 109 ]. Methionine and cysteine can affect glutathione levels which prevent the negative effects of ROS and apoptosis in embryos [ 29 , 80 , 118 , 135 , 136 ]. Recent evidence suggested that the polarized protein like leptin and signal transducer and activator of transcription 3 (STAT3) and maybe beta-actin and IL-1 mRNAs can display polarized distribution in oocytes [ 137 139 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methionine is the initiating amino acid for the synthesis of proteins in eukaryotes [488,489]. Preimplantation bovine embryos are able uptake methionine from its environment [490], and the absence of methionine in the culture media reduced blastocyst rate in bovine embryos produced in vitro [491]. Methionine is also important for controlling oxidative stress, as it can be metabolized into cysteine, that along with glutamate and glycine are precursors of glutathione (GSH) [492,493], a major antioxidant in mammalian cells [161].…”
Section: Discussionmentioning
confidence: 99%